Comprehensive Physiology 2012
DOI: 10.1002/cphy.c100088
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Biological Clocks and Rhythms

Abstract: Animals, plants, and microorganisms exhibit numerous biological rhythms that are generated by numerous biological clocks. This article summarizes experimental data pertinent to the often-ignored issue of integration of multiple rhythms. Five contexts of integration are discussed: (i) integration of circadian rhythms of multiple processes within an individual organism, (ii) integration of biological rhythms operating in different time scales (such as tidal, daily, and seasonal), (iii) integration of rhythms acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 561 publications
0
24
0
1
Order By: Relevance
“…Such a phenomenon was clearly observed in only a few individuals (n = 4). Interestingly, splitting (the presence of two separate phase components 180° apart) in mammalian model organisms is usually observed in a minority of tested individuals (Refinetti 2006). The optimization of physiological processes through the spectral coordination of diel and tidal rhythms has not received sufficient attention (Refinetti 2012), but it could be used as a determinant to assess the ecological significance of biological rhythms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a phenomenon was clearly observed in only a few individuals (n = 4). Interestingly, splitting (the presence of two separate phase components 180° apart) in mammalian model organisms is usually observed in a minority of tested individuals (Refinetti 2006). The optimization of physiological processes through the spectral coordination of diel and tidal rhythms has not received sufficient attention (Refinetti 2012), but it could be used as a determinant to assess the ecological significance of biological rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, splitting (the presence of two separate phase components 180° apart) in mammalian model organisms is usually observed in a minority of tested individuals (Refinetti 2006). The optimization of physiological processes through the spectral coordination of diel and tidal rhythms has not received sufficient attention (Refinetti 2012), but it could be used as a determinant to assess the ecological significance of biological rhythms. Finally, we cannot exclude the possibility that a higher current speed and lower light intensity (simulating deeper water) could be more effective in eliciting such phenomena in a higher proportion of lobsters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on rewards and inhibits, which are aspects of conventional EEG frequency training, but these concepts no longer make sense at such low frequencies (the current Cygnet software, version 2.0.7.4, can now filter out frequencies as low as 0.0001 mHz, which is approximately one cycle per 116 days). Even though there are biorhythms that are as slow and slower than the current limit of detection by this EEG amplifier [95], there are no known neural or glial origins of these very slow oscillations, causing controversy over the source of the signal [65,76,97]. However, a recent study demonstrated that 20 sessions of ILF neurofeedback training increased the power of all of the ILFs (≤ 0.1 Hz), including the typical peak around 0.01-0.1 Hz, which is called the infra-slow oscillation (ISO) and correlates with the BOLD signal [98,99].…”
Section: Infra-low Frequency Trainingmentioning
confidence: 99%
“…The most well-known method is fMRI training, which monitors the BOLD signal in brain structures with high spatial resolution [91][92][93]. Other hemodynamic-based methods that are less well-known are hemoencephalographic (HEG) training and functional near-infrared spectroscopy (FNIRS) training, which have less spatial resolution than fMRI but greater than that of EEG [67,94,95]. FMRI neurofeedback has the greatest number of gold standard RCTs, likely due to the fact that the principal investigators on those studies typically are medical doctors and tend to receive more funding than nonmedical doctors [91,93].…”
Section: Hemodynamics-based Trainingmentioning
confidence: 99%